The last scream - Stine, R. L. (Pocket Books, 1996)
Robin Fear is out to destroy Dierdre Bradley, her father, and Fear Park but one person's waiting for revenge.
Keywords: Amusement parks -- Fiction; Horror tales; Revenge -- Fiction